My reasons for translating Shakespeare - Barbara Heliodora (Ilha do Desterro)
Being now in the finishing stages of my fifteenth translation of a play by William Shakespeare it is somewhat embarrassing that for the first time I should be asking myself in all seriousness why I do it at all. Loving the plays, of course, is not it, since I loved them for many years without translating them, and many people love them without ever getting the urge to translate them into another language. On the other hand, I must say that I never, at any moment, made the awesome decision to become by definition a translator of Shakespeare’s plays, and so it will have to be admitted that a whole set of circumstances must have contributed to what in fact took place—and, I am sure, also weighed considerably as to the type of translation that I have been trying to make all these years.